MatSWMM – An open-source toolbox for designing real-time control of urban drainage systems. (September 2016) - Riaño-Briceño, G.; Barreiro-Gomez, J.; Ramirez-Jaime, A.; Quijano, N.; Ocampo-Martinez, C.
Abstract: This manuscript describes the MatSWMM toolbox, an open-source Matlab, Python, and LabVIEW-based software package for the analysis and design of real-time control (RTC) strategies in urban drainage systems (UDS). MatSWMM includes control-oriented models of UDS, and the storm water management model (SWMM) of the US Environmental Protection Agency (EPA), as well as systematic-system edition functionalities. Furthermore, MatSWMM is also provided with a population-dynamics-based controller for UDS with three of the fundamental dynamics, i.e., the Smith, projection, and replicator dynamics. The simulation algorithm, and a detailed description of the features of MatSWMM are presented in this manuscript in order to illustrate the capabilities that the tool has for educational and research purposes. Highlights: An open-source toolbox for real-time control in drainage systems has been developed. The toolbox includes a distributed population-dynamics-based controller. The toolbox runs on Python, Matlab, and LabVIEW. The features of MatSWMM make it suitable for both educational and research purposes.